Delivery of bioencapsulated proteins - Nor Hasmaliana, Abdul Manas; Dayang Norulfairuz, Abang Zaidel; Nur Izyan, Wan Azelee; Siti Fatimah Zaharah, Mohd Fuzi; Aizi Nor Mazila, Ramli; Shalyda, Md Shaarani; Rosli, Md. Illias; Norsuhada, Abdul Karim (Elsevier, 2023)
Proteins and peptides have been used in pharmaceutical, nutraceutical, and food applications for their therapeutic and nutritional properties. However, administration of these molecules to the human body is challenging due to their low stability, low bioavailability, high biodegradability, immunogenicity, and inefficient permeability. These molecules require a tailored delivery system to ensure bioavailability and efficient maintenance to target location. Nanotechnology has emerged as an ideal platform in drug delivery as it provides a versatile system with excellent biocompatibility. This chapter discusses various nanomaterials that have been explored, particularly organic, inorganic, protein, and hybrid nanomaterials which are biocompatible for administration to human body. Challenges for the development of protein in nanomaterials are outlined and strategies for the nanoencapsulation in these nano-vehicles are discussed that aim for preservation of bioactivity, high protein loading, structural stability, permeability, and control release besides being easy for synthesis and cost-effective.